2003
DOI: 10.1046/j.1365-294x.2003.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and gene flow in a metapopulation of an endangered plant species,Silene tatarica

Abstract: We investigated the distribution of genetic variation within and between seven subpopulations in a riparian population of Silene tatarica in northern Finland by using amplified fragment length polymorphism (AFLP) markers. A Bayesian approach-based clustering program indicated that the marker data contained not only one panmictic population, but consisted of seven clusters, and that each original sample site seems to consist of a distinct subpopulation. A coalescent-based simulation approach shows recurrent gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
238
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(271 citation statements)
references
References 66 publications
(67 reference statements)
28
238
5
Order By: Relevance
“…Kudoh and Whigham (1997), for example, found high gene flow among populations that were adjacent to the tidal stream, indicating that these populations may function as a single genetic metapopulation by extensive and long-distance seed exchanges between them. Similarly, Tero et al (2003) also found no isolation by distance and no regional structure indicating frequent longdistance seed exchange. On the other hand, nearby populations formed clear clusters in the UPGMA dendrogram, which suggests that short-distance seed dispersal or pollen flow among nearby populations may affect the structure of genetic variation in the studied metapopulation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Kudoh and Whigham (1997), for example, found high gene flow among populations that were adjacent to the tidal stream, indicating that these populations may function as a single genetic metapopulation by extensive and long-distance seed exchanges between them. Similarly, Tero et al (2003) also found no isolation by distance and no regional structure indicating frequent longdistance seed exchange. On the other hand, nearby populations formed clear clusters in the UPGMA dendrogram, which suggests that short-distance seed dispersal or pollen flow among nearby populations may affect the structure of genetic variation in the studied metapopulation.…”
Section: Discussionmentioning
confidence: 89%
“…In Populus nigra, a riparian pioneer tree species that was studied along the Drô me River, the F ST value was 0.047 (Imbert and Lefèvre, 2002). Only in the case of the riparian plant Silene tatarica, genetic differentiation appeared to be substantially higher (y B ¼ 0.287) (Tero et al, 2003). Recent populations located in the immediate vicinity of the river, where extinction-colonization events are recurrent features of the species ecology, had lower levels of genetic differentiation than populations located in the winter bed of the river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several basic hypotheses of migration patterns with contrasting predictions can be derived for population structure among such linearly arranged plant subpopulations (see e.g. Tero et al 2003). First, despite the apparent spatial subpopulation structure the patches may form a single panmictic unit with free gene flow throughout the genetically uniform population.…”
Section: Introductionmentioning
confidence: 99%
“…1.0) was used to estimate parameters related to genetic structure (Theta B value) (Tero et al 2003).…”
Section: Molecular Analysesmentioning
confidence: 99%